2x+6=11+x

Simple and best practice solution for 2x+6=11+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6=11+x equation:


Simplifying
2x + 6 = 11 + x

Reorder the terms:
6 + 2x = 11 + x

Solving
6 + 2x = 11 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
6 + 2x + -1x = 11 + x + -1x

Combine like terms: 2x + -1x = 1x
6 + 1x = 11 + x + -1x

Combine like terms: x + -1x = 0
6 + 1x = 11 + 0
6 + 1x = 11

Add '-6' to each side of the equation.
6 + -6 + 1x = 11 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = 11 + -6
1x = 11 + -6

Combine like terms: 11 + -6 = 5
1x = 5

Divide each side by '1'.
x = 5

Simplifying
x = 5

See similar equations:

| 22-5(6v-1)=57 | | 2(x+3)=11x | | Px+Q=46x+23P | | 11x+6+105=180 | | 7x+151=-5x-83 | | 4k+(-14)+3k=21 | | 4.9t^2+2.1t-55=0 | | 8x+2=10+4x | | v=1/3(3.14)(36)(8) | | 2cos^2(2x)-7cos(2x)-9=0 | | 3xsquared+4=16 | | 12x+8=14x-8 | | 2=k*3+4 | | -4=8x-10y | | 3.4x+3-1.3x=11.4 | | 10x+(-11)+(-4x)=43 | | v=1/3(3.14)(144)(8) | | v=1/3(3.14)(196)(10) | | 12x^2+443+144y=0 | | -1000x^3+7500X=0 | | 14k+(-14)+3k=21 | | -(5-6x)=4(5x+6) | | 3-(6-2x)=4 | | 7.5x+2=15.5x | | (12-8x)+(3x+12)=0 | | 21x+10=180 | | 4(w-6)=3(x+1) | | 8x+y=8fory | | s=2(3.14)rh+2(3.14)r^2 | | -x-4=0.6x+4 | | X^2-4x+6=o | | 4y-5x=3y-11+2x |

Equations solver categories